Conflict and the practice of Christian faith: the Anglican experiment - Kaye, Bruce Norman (Cascade Books, 2009)
Conflict and connection in early Christianity -- Local traditions and the universal church -- Catholicity without Leviathan -- The powers, church, and truth -- Why the "Virginia report" is not good enough -- The Windsor report: the questions less asked -- Will the Windsor process lead to the precipice? -- Lambeth: a conference re-discovered? -- Conflict, catholicityand hope.